Determinants of Risk and Uncertainty in Oil Palm Nursery (2019)
This paper investigates the distributional effect of income among rural farm households in Nigeria.A quantile regression approach was applied on cross-section data from a nationally representative data. Ordinary least square was also used for comparison purposes. Results show that household size, asset ownership, farm size, extension services and access to credit were the most important factors explaining income distribution across quantiles but with varying magnitude.Additionally, across methods of estimation, assets ownership, farm size, extension service and household size were consistent variables that influenced farm household income. We found that factors that determines income distribution among farm households was different suggesting covariates are not constant across quantiles. This paper puts forward relevant policy options suitable for improved household livelihood